Strategi Pengembangan Kepuasan Konumen Melalui Jasa Karyawan Perusahaan Jasa - MOYO JALADRI, CHAVID; LUCY KRISTIAN, ERIVINA (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2025)
This research to determine job satisfaction through turnover intention. Turnover intention is a critical concern that cannot be ignored in business. Many businesses are still experiencing turnover intention problems in this era of globalization. As a result of this problem, some groups in the association have chosen to leave or move from their ongoing work environment. Indomaret is one of the organizations affected by this problem. This study aims to determine the impact of fair job fulfillment and square of Turner expectations of Indomaret representatives. This study uses a quantitative methodology strategy. The sample used is 7 individuals. The source of information is obtained from important information by distributing surveys. The information investigation strategy used is a basic recurrence examination. From the consequences of the review, it can be assumed that job fulfillment hurts the level of representative turnover goals; assuming low position fulfillment, the level of representative turnover expectations will increase. As a general rule, workplace, work, and responsibility also basically affect the representative workplace.